2014
DOI: 10.1111/jgh.12767
|View full text |Cite
|
Sign up to set email alerts
|

Importance of cyclooxygenase‐1/prostacyclin in modulating gastric mucosal integrity under stress conditions

Abstract: Background and Aim: We investigated the roles of cyclooxygenase (COX) isozymes and prostaglandins (PGs) and their receptors in mucosal defense against cold-restraint stress (CRS)-induced gastric lesions. Methods: Male C57BL/6 wild-type (WT) mice and those lacking COX-1 or COX-2 as well as those lacking EP1, EP3, or IP receptors were used after 18 h fasting. Animals were restrained in Bollman cages and kept in a cold room at 10°C for 90 min. Results: CRS induced multiple hemorrhagic lesions in WT mouse stomachs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…In this study, we found that both COX-1 and COX-2 expressions were decreased in SII-Reb and SII-Sal groups at day 5, which indicated that the inhibition of COX (including both COX-1 and COX-2) might underlie the mechanism of aspirin-induced SII ( Fig 4A–4F ). Some investigators suggested that COX-1 to a greater extent than COX-2 contributes to gastric PGE 2 production [ 37 ]. But Castlestone et al demonstrated that, in the intestinal mucosa, the increased production of PGE 2 depended more on COX-2 than on COX-1 [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that both COX-1 and COX-2 expressions were decreased in SII-Reb and SII-Sal groups at day 5, which indicated that the inhibition of COX (including both COX-1 and COX-2) might underlie the mechanism of aspirin-induced SII ( Fig 4A–4F ). Some investigators suggested that COX-1 to a greater extent than COX-2 contributes to gastric PGE 2 production [ 37 ]. But Castlestone et al demonstrated that, in the intestinal mucosa, the increased production of PGE 2 depended more on COX-2 than on COX-1 [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the PGE 2 inhibiting effects of KIT 17 and most likely by the other KIT compounds is not due a direct inhibition of COX activity. The COX-1 inducing effects might even have positive benefits, since COX-1 is protecting the gut mucosa and its inhibition by some NSAIDs cause gastro-intestinal side effects [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results are, to some extent, in agreement with the data obtained by Tanaka et al (2007) [28] who demonstrated that mild stress protects against CRS-induced gastric ulceration by PGs derived from both COX-1 and COX-2 through activation of phospholipase A2. Furthermore, Amagase et al (2014) [29] revealed that PGs derived from COX-1 play an important role in the gastric mucosal defense during CRS. On the contrary, it has been reported that COX-2 plays a crucial role in gastric mucosal defense [30].…”
Section: Discussionmentioning
confidence: 99%